Length-based stock assessment in small-scale multi-gear fisheries: insights from a European hotspot (NW Spain) - Daniel García-García; Marta Cousido-Rocha; Rafael Bañón; José Manuel Campelos; Fernando Quintero; Asunción Gancedo; Fabio Lamas; Alberto Otero; Angel Rodríguez; Alexandre Alonso-Fernández (Reviews in Fish Biology and Fisheries, 2026)

Microbially influenced uranium biomineralization and mineralogical changes in a U(VI)/carbon steel/bentonite system for repository safety assessment - Cristina Povedano-Priego; Miguel Angel Ruiz-Fresneda; Fadwa Jroundi; Lidia Lopez-Tercero; Laura Carmen Terrón-Camero; Marta Espinar-Solano; Ursula Alonso; Ana M. Fernández; Jesus J. Ojeda; Mohamed L. Merroun (Journal of Hazardous Materials, 2026)

Diplopia possibly induced by safinamide in parkinson’s disease - Hortensia Alonso-Navarro; Miguel Angel Martín-Gómez; Margarita Arroyo-Solera; Silvina Espada-Rubio; Paula Salgado-Cámara; Félix Javier Jiménez-Jiménez (Acta Neurologica Belgica, 2026)

Performance assessment of no-fee GNSS augmentation systems for tractor guidance - Jaime Gomez-Gil; Angel Alonso-Garcia; Sergio Alonso-Garcia; Fco. Javier Gomez-Gil (Computers and Electronics in Agriculture, 2026)

Controlled synthesis of graphene oxide by electrochemical exfoliation for advanced nanofiltration membranes - Raul Pla; Daniel Fernandez-Carrasco; Silvia Villar-Rodil; Jose Alberto Baeza; Luisa Calvo; Noelia Alonso-Morales; Miguel Angel Gilarranz; Fabian Suarez-García; Juan Ignacio Paredes (Journal of Environmental Chemical Engineering, 2026)

Exploring the role of microalgae in alleviating metabolic syndrome: Insights from murine models and human trials on obesity, diabetes, and cardiovascular disorders - Alba Domínguez-Encinas; Blanca Pardo de Donlebún; Laura Alonso-Pintre; Pilar Gómez-Cortés; Blanca Hernández-Ledesma; Miguel Angel de la Fuente (Algal Research, 2026)

Correction: Anti-inflammatory, antioxidant, and antinociceptive properties of methanolic flower extracts of Tecoma stans: a promising natural therapeutic agent - Abril Bernardette Martínez-Rizo; Oscar Isaac Correa-Polanco; Valeria García-Martínez; Fabiola Villa-de la Torre; Mario Alberto Ramírez-Camacho; Rocio Borges-Argáez; Eunice Yáñez-Barrientos; Alan Alexander Gonzalez-Ibarra; Angel Josabad Alonso-Castro; Claribel Huchin Chan; Victor Ermilo Arana-Argáez (Inflammopharmacology, 2026)

Anti-inflammatory, antioxidant, and antinociceptive properties of methanolic flower extracts of Tecoma stans: a promising natural therapeutic agent - Abril Bernardette Martínez-Rizo; Oscar Isaac Correa-Polanco; Valeria García-Martínez; Fabiola Villa-de la Torre; Mario Alberto Ramírez-Camacho; Rocio Borges-Argáez; Eunice Yáñez-Barrientos; Alan Alexander Gonzalez-Ibarra; Angel Josabad Alonso-Castro; Claribel Huchin Chan; Victor Ermilo Arana-Argáez (Inflammopharmacology, 2026)

Burning mouth syndrome and dysgeusia possibly induced by rifamixine - Hortensia Alonso-Navarro; Margarita Arroyo-Solera; Miguel Angel Martín-Gómez; Paula Salgado-Cámara; Alba Cárcamo-Fonfría; Félix Javier Jiménez-Jiménez (Acta Neurologica Belgica, 2026)

Removal of PFAS from complex matrix water by filtration with supported graphene oxide membranes - Raul Pla; Noelia Alonso-Morales; Jose Alberto Baeza; Luisa Calvo; Miguel Angel Gilarranz (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Glyphosate behavior in rice paddy fields across different rotation systems” [Sci. Total Environ. 995 (2025) 180069] - Beatriz Alonso Vignola; Angel Manuel Segura; Lucía Pareja; Sebastián Martínez; Alvaro Roel; José Terra; Leonidas Carrasco-Letelier; Andrés Pérez-Parada (Science of The Total Environment, 2025)

Glyphosate behavior in rice paddy fields across different rotation systems - Beatriz Alonso Vignola; Angel Manuel Segura; Lucía Pareja; Sebastián Martínez; Alvaro Roel; José Terra; Leonidas Carrasco-Letelier; Andrés Pérez-Parada (Science of The Total Environment, 2025)

Correction to: Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández‑Pérez; Joan Jiménez‑Balado; Adrià Macias‑Gómez; Antoni Suárez‑Pérez; Marta Vallverdú‑Prats; Alberto Pérez‑Giraldo; Marc Viles‑García; Julia Peris‑Subiza; Sergio Vidal‑Notari; Eva Giralt‑Steinhauer; Daniel Guisado‑Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Chemical and nutraceutical characterization of coproducts obtained during the protein concentrate preparation from azufrado common (Phaseolus vulgaris) bean grains - Laura Gabriela Espinosa-Alonso; Jocelyn de Jesús Gálvez-Morales; Chibuike C. Udenigwe; Alma Leticia Martinez-Ayala; Maribel Valdez-Morales; Angel Valdez-Ortiz; Sergio Medina-Godoy (Biocatalysis and Agricultural Biotechnology, 2025)

Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández-Pérez; Joan Jiménez-Balado; Adrià Macias-Gómez; Antoni Suárez‑Pérez; Marta Vallverdú-Prats; Alberto Pérez-Giraldo; Marc Viles-García; Julia Peris-Subiza; Sergio Vidal-Notari; Eva Giralt-Steinhauer; Daniel Guisado-Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Anti-inflammatory effects of a methanol extract from Montanoa grandiflora DC. (Asteraceae) leaves on in vitro and in vivo models - Mariana Sánchez-Canul; Fabiola Villa-de la Torre; Rocío Borges-Argáez; Claribel Huchin-Chan; Guillermo Valencia-Pacheco; Eunice Yáñez-Barrientos; Michelle Romero-Hernández; Angel Josabad Alonso-Castro; Víctor Ermilo Arana-Argáez (Inflammopharmacology, 2025)

Exploring structural and computational contrasts in Myoglobins: Implications for thermal treatment-induced Sulfmyoglobin formation - Juan C. Ramírez-Suárez; Andrés Álvarez-Armenta; Jose Angel Huerta-Ocampo; Alonso A. López-Zavala; David O. Corona-Martínez; Rogerio R. Sotelo-Mundo; Ramón Pacheco-Aguilar (Food Chemistry, 2024)

Epidemiology of marine turtle fibropapillomatosis and tumour-associated chelonid alphaherpesvirus 5 (ChHV5; Scutavirus chelonidalpha5) in North-Western Mexico: a scoping review implementing the one health approach - Joelly Espinoza; Alonzo Alfaro-Núñez; Carlos Cedillo-Peláez; Helena Fernández-Sanz; Agnese Mancini; Alan A. Zavala-Norzagaray; Cesar Paul Ley-Quiñonez; Erika Santacruz López; Miguel Angel Garcia-Bereguiain; A. Alonso Aguirre; Eduardo Reséndiz (Veterinary Research Communications, 2024)
Fibropapillomatosis (FP) - tumour-associated chelonid alphaherpesvirus 5 (ChHV5; Scutavirus chelonidalpha5) - is a disease that affect marine turtles around the world, and characterized by the formation of cutaneous tumours that can appear anywhere on the body. We carried out a thorough literature search (from 1990 to 2024) in the feeding sites of North-western Mexico, a region that hosts important habitats for feeding, development, and reproduction for five of the seven existing sea turtle species. We found 18 reports recording a total of 32 cases of FP and/or ChHV5/Scutavirus chelonidalpha5 in coastal and insular areas of North-western Mexico. Baja California Sur resulted with the highest number of cases (75%). While the first case of ChHV5/Scutavirus chelonidalpha5 infection was reported in 2004, the presence of FP tumours was reported in 2014 and became more frequent between 2019 and 2024. The affected species were black, Chelonia mydas (50%), olive ridley, Lepidochelys olivacea (46.8%) and loggerhead turtles, Caretta caretta (3.2%). Tumours occurred mainly in anterior flippers (46.1%) and neck (22.5%), and most had a nodular and verrucous appearance with a rough surface. In the study region, there is a potential sign of the emergence of the ChHV5/Scutavirus chelonidalpha5 infections and FP disease during the last 20 years, with a rapid increase during the last 10 years. As long as infections by ChHV5/Scutavirus chelonidalpha5 and the prevalence of the FP disease may be potentially influenced by anthropogenic activities, a One Health approach is needed to understand and improve sea turtles’ health.

Focal dystonia triggered by tarsal tunnel syndrome as the presenting sign of parkinson’s disease - Hortensia Alonso-Navarro; Estefanía Cantador-Pavón; Vicente Gajate-García; Miguel Angel Martín-Gómez; Félix Javier Jiménez-Jiménez (Acta Neurologica Belgica, 2024)

Magnetic micro-archaeology: a method for conducting rock magnetic microfacies analysis on archaeological soil micromorphology samples, with a case study from El Salt, Alcoy, Spain - Ada Dinçkal; Angel Carrancho Alonso; Cristo M. Hernandez Gomez; Carolina Mallol (Archaeological and Anthropological Sciences, 2024)
For geoarchaeologists the use of multiproxy and multimethod integrative approaches has become common for studying the sedimentary context of archaeological materials. In this paper, we introduce a novel approach that combines rock magnetic analysis with micromorphological analysis. We first conduct a brief examination of the magnetic properties of organic resins used in micromorphology to understand the potential impact of the resin and manufacturing process on the magnetic signature. It is crucial to understand the original production of the samples to ensure that endothermic reactions do not compromise the magnetic data. We illustrate the advantages of this approach through a case study of a pit hearth from the Neanderthal archaeological site of El Salt in Alcoi, Spain. This study utilises archived micromorphological samples of a pit hearth (combustion structure H77) initially described by Leierer et al. (J Archaeol Sci 123:105237, 2020). Rock magnetic analysis of multiple magnetic parameters—including magnetic susceptibility, natural remanent magnetization, and progressive isothermal remanent magnetization—reveals that each microfacies type exhibits a unique magnetic pattern, even if there is overlapping in signatures across some magnetic parameters. The interpretation of the magnetic data aligns with the results and microfacies descriptions previously provided by Leierer et al. (J Archaeol Sci 123:105237, 2020), further supporting the interpretation of the combustion feature as being in situ with a history of repeated use. The approach presented here offers an enhanced tool for micromorphologists to better understand the magnetic characteristics of microfacies units in higher resolution and establish direct connections to the micromorphological results.

Invertase production by Rhodotorula toruloides in submerged and surface adhesion on magnetic nanoparticles fermentations - Dania Alonso-Estrada; Nayra Ochoa-Viñals; Rodolfo Ramos-González; Georgina Michelena-Álvarez; Gilberto Francisco Hurtado-López; Arianna Núñez-Caraballo; Miguel Angel Aguilar-González; Anna Ilyina (Biocatalysis and Agricultural Biotechnology, 2024)

Single cell ICP-MS to evaluate the interaction behaviour for Cd, Ce and U with Streptomyces coelicolor spores - Steffen Hellmann; Paula García-Cancela; Sergio Alonso-Fernández; Mario Corte-Rodríguez; Jörg Bettmer; Angel Manteca; Dirk Merten; Teba Gil-Díaz; Thorsten Schäfer; María Montes-Bayón (Chemosphere, 2024)

Blood biochemistry reference values for nesting Kemp's ridley turtles (Lepidochelys kempii) in Rancho Nuevo Sanctuary, Mexico - Valeria Leal-Sepúlveda; Miguel Angel Reyes-López; Fátima Yedith Camacho-Sánchez; Héctor Hugo Acosta-Sánchez; Kevin Alan Zavala-Félix; Catherine E. Hart; Alan A. Zavala-Norzagaray; Renato Leal-Moreno; Brenda Aracely Espinoza-Romo; A. Alonso Aguirre; Juan Carlos Sainz-Henández; César P. Ley-Quiñónez (Estuarine, Coastal and Shelf Science, 2023)

Transgenic HPV11-E2 protein modulates URR activity in vivo - Shubei Wang; Vera Gramm; Elke Laport; Tim Holland-Letz; Angel Alonso; Johannes Schenkel (Transgenic Research, 2023)
In vitro experiments have shown that the E2 protein of human papillomaviruses (HPV) binds to the upstream regulatory region (URR) of the viral genome and modulates transcription. Additionally, it seems to be a necessary component for viral DNA replication together with E1. We have developed a transgenic mouse model containing the URR region of the low-risk virus HPV11 that regulates the expression of the lacZ reporter gene. Most interestingly, in these mice, the transgene was exclusively expressed in the bulge region of the hair follicle but not in any other tissues. Further experimental data indicate that in double transgenic mice that also express the HPV11-E2 protein under the control of the Ubiquitin C-promoter, the transcription of the reporter gene is modulated. When E2 is present, the expression of the reporter gene also occurs exclusively in the bulge region of the hair follicles as it does in the single transgenic mice, but the expression of the lacZ driven by the URR is increased and the statistical spread is greater. Even if the expression of the reporter gene occurs in the hair follicles of the dorsal skin of an animal uniform, E2 obviously has the capacity for both to induce and to repress the URR activity in vivo.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Micropropagation of Catasetum integerrimum Hook (Orchidaceae) through seed germination and direct shoot regeneration from pseudobulbs and roots - Luis J. Castillo-Pérez; Angel Josabad Alonso-Castro; Javier Fortanelli-Martínez; Candy Carranza-Álvarez (In Vitro Cellular & Developmental Biology - Plant, 2022)

Emergence and spread of the potential variant of interest (VOI) B.1.1.519 of SARS-CoV-2 predominantly present in Mexico - Abril Paulina Rodríguez-Maldonado; Joel Armando Vázquez-Pérez; Alberto Cedro-Tanda; Blanca Taboada; Celia Boukadida; Claudia Wong-Arámbula; Tatiana Ernestina Nuñez-García; Natividad Cruz-Ortiz; Gisela Barrera-Badillo; Lucía Hernández-Rivas; Irma López-Martínez; Alfredo Mendoza-Vargas; et al. (Archives of Virology, 2021)

Antinociceptive and anti-inflammatory effects of Cuphea aequipetala Cav (Lythraceae) - Angel Josabad Alonso-Castro; Victor Arana-Argáez; Eunice Yáñez-Barrientos; Mario Alberto Ramírez-Camacho; Katarzyna Wrobel; Julio Cesar Torres-Romero; Carolina León-Callejas; Kazimierz Wrobel (Inflammopharmacology, 2021)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Central nervous system evaluation of an ethanol extract of Bidens odorata Cav (Asteraceae) leaves, and its antinociceptive interaction with paracetamol and naproxen - Angel Josabad Alonso-Castro; Juan Ramón Zapata-Morales; Cesar Solorio-Alvarado; Andrea Hernández-Santiago; Luis Antonio Espinoza-Ramírez; Candy Carranza-Álvarez; Velayudham Ramadoss (Inflammopharmacology, 2020)

Anti-inflammatory and antinociceptive effects of an ethanol extract from Senna septemtrionalis - Víctor Ermilo Arana-Argáez; Fabiola Domínguez; Diego A. Moreno; Mario Alberto Isiordia-Espinoza; Julio Cesar Lara-Riegos; Emanuel Ceballos-Góngora; Juan Ramón Zapata-Morales; Lorenzo Franco-de la Torre; Sergio Sánchez-Enríquez; Angel Josabad Alonso-Castro (Inflammopharmacology, 2020)

Some toxic metals (Al, As, Mo, Hg) from cow’s milk raised in a possibly contaminated area by different sources - José-Ramiro González-Montaña; Enrique Senís; Angel-Javier Alonso; Marta-Elena Alonso; María-Pilar Alonso; Juan-Carlos Domínguez (Environmental Science and Pollution Research, 2019)

BetaHPV E6 and E7 colocalize with NuMa in dividing keratinocytes - Evelyn Oswald; Matthias Kirschberg; François Aubin; Angel Alonso; Martin Hufbauer; Baki Akgül; Eeva Auvinen (Virus Genes, 2019)

Total synthesis of the linear and angular 3-methylated regioisomers of the marine natural product Kealiiquinone and biological evaluation of related Leucetta sp. alkaloids on human breast cancer - César R. Solorio-Alvarado; Velayudham Ramadoss; Rocío Gámez-Montaño; Juan R. Zapata-Morales; Angel J. Alonso-Castro (Medicinal Chemistry Research, 2019)

The endemic orchids of Mexico: a review - Luis J. Castillo-Pérez; Domingo Martínez-Soto; Juan J. Maldonado-Miranda; Angel J. Alonso-Castro; Candy Carranza-Álvarez (Biologia, 2019)

Isotopic evidence for the reconstruction of diet and mobility during village formation in the Early Middle Ages: Las Gobas (Burgos, northern Spain) - Iranzu Guede; Luis Angel Ortega; Maria Cruz Zuluaga; Ainhoa Alonso-Olazabal; Xabier Murelaga; José Luis Solaun; Iban Sanchez; Agustín Azkarate (Archaeological and Anthropological Sciences, 2018)

Synthesis and evaluation of antinociceptive and anti-inflammatory effects of nitro-porphyrins - Juan Ramón Zapata-Morales; Cuauhtémoc Pérez-González; Angel Josabad Alonso-Castro; Miguel Martell-Mendoza; Abigail Hernández-Munive; Salud Pérez-Gutiérrez (Medicinal Chemistry Research, 2018)

Human papillomavirus type 8 E7 protein binds nuclear myosin 1c and downregulates the expression of pre-rRNA - Evelyn Oswald; Eileen Reinz; Renate Voit; François Aubin; Angel Alonso; Eeva Auvinen (Virus Genes, 2017)

A Method for the Annotation of Functional Similarities of Coding DNA Sequences: the Case of a Populated Cluster of Transmembrane Proteins - Miguel Angel Fuertes; José Ramón Rodrigo; Carlos Alonso (Journal of Molecular Evolution, 2017)

From Science to Policy and Society: Enhancing the Effectiveness of Communication - Marianna Mea; Alice Newton; Maria C. Uyarra; Carolina Alonso; Angel Borja (Frontiers in Marine Science, 2016)

Do Intron and Coding Sequences of Some Human–Mouse Orthologs Evolve as a Single Unit? - Miguel Angel Fuertes; José Ramón Rodrigo; Carlos Alonso (Journal of Molecular Evolution, 2016)

Mutation of Human Connexin43 Amino Acids S279/S282 Increases Protein Stability Upon Treatment with Epidermal Growth Factor - Melanie Schmitt; Kerstin Leykauf; Eileen Reinz; Hao Cheng; Angel Alonso; Johannes Schenkel (Cell Biochemistry and Biophysics, 2014)

A methodological improvement for assessing petrochemical projects through life cycle assessment and eco-costs - Miguel Angel Morales Mora; Elena Rosa Dominguez; Alonso Aguilar Ibarra; Nydia Suppen Reynaga; Sergio Alejandro Martínez Delgadillo (The International Journal of Life Cycle Assessment, 2014)

Development of the serotonergic cells in murine raphe nuclei and their relations with rhombomeric domains - Antonia Alonso; Paloma Merchán; Juan E. Sandoval; Luisa Sánchez-Arrones; Angels Garcia-Cazorla; Rafael Artuch; José L. Ferrán; Margaret Martínez-de-la-Torre; Luis Puelles (Brain Structure and Function, 2013)

Removal and Accumulation of As, Cd and Cr by Typha latifolia - Adriana Leura-Vicencio; Angel Josabad Alonso-Castro; Candy Carranza-Álvarez; René Loredo-Portales; Ma Catalina Alfaro-De la Torre; Ramón Fernando García-De la Cruz (Bulletin of Environmental Contamination and Toxicology, 2013)

The effect of BDNF val66met polymorphism on visuomotor adaptation - Raed A. Joundi; Virginia Lopez-Alonso; Angel Lago; John-Stuart Brittain; Miguel Fernandez-del-Olmo; Pilar Gomez-Garre; Pablo Mir; Ned Jenkinson; Binith Cheeran; Peter Brown (Experimental Brain Research, 2012)

Eastern boundary drainage of the North Atlantic subtropical gyre - Irene Laiz; Jose Luis Pelegrí; Francisco Machín; Pablo Sangrà; Alonso Hernández-Guerra; Angeles Marrero-Díaz; Angel Rodríguez-Santana (Ocean Dynamics, 2012)

Semifield assessment of the runoff potential and environmental risk of the parasiticide drug ivermectin under Mediterranean conditions - Carlos Fernández; Miguel Angel Porcel; Alvaro Alonso; Manuel San Andrés; José Vicente Tarazona (Environmental Science and Pollution Research, 2011)

Nitrogen compounds in embryogenic and non-embryogenic calluses of Medicago arborea L. - Elena Gutierrez; Piedad Gallego; Angel Alonso; Antonio Blazquez; Luisa Martin; Javier Fernandez; Leticia Dominguez; Cristina Rioja; Hilario Guerra; Nieves Villalobos (In Vitro Cellular & Developmental Biology - Plant, 2010)

Melatonin attenuates the acetylcholine-induced contraction in isolated intestine of a teleost fish - Elena Velarde; Angel Luis Alonso-Gómez; Clara Azpeleta; Esther Isorna; María Jesús Delgado (Journal of Comparative Physiology B, 2009)

Removal and Accumulation of Cadmium and Lead by Typha latifolia Exposed to Single and Mixed Metal Solutions - Angel Josabad Alonso-Castro; Candy Carranza-Álvarez; Ma Catalina Alfaro-De la Torre; Leonardo Chávez-Guerrero; Ramón Fernando García-De la Cruz (Archives of Environmental Contamination and Toxicology, 2009)

Plant remains, storage and crop processing inside the Iron Age fort of Els Vilars d’Arbeca (Catalonia, Spain) - Natàlia Alonso; Emili Junyent; Angel Lafuente; Joan B. López (Vegetation History and Archaeobotany, 2008)

Accumulation and Distribution of Heavy Metals in Scirpus americanus and Typha latifolia from an Artificial Lagoon in San Luis Potosí, México - Candy Carranza-Álvarez; Angel Josabad Alonso-Castro; María Catalina Alfaro-De La Torre; Ramón Fernando García-De La Cruz (Water, Air, & Soil Pollution, 2008)

Expression of the HPV11 E2 gene in transgenic mice does not result in alterations of the phenotypic pattern - Kerstin Leykauf; Kirsten Kabsch; Nikolaus Gassler; Lutz Gissmann; Angel Alonso; Johannes Schenkel (Transgenic Research, 2008)

Multiple Conductance Substates in Pharmacologically Untreated Na+ Channels Generating Persistent Openings in Rat Entorhinal Cortex Neurons - Jacopo Magistretti; Angel Alonso (The Journal of Membrane Biology, 2006)

Disentangling the molecular mechanisms of action of endogenous and environmental estrogens - Angel Nadal; Paloma Alonso-Magdalena; Cristina Ripoll; Esther Fuentes (Pflügers Archiv - European Journal of Physiology, 2005)

Calcium-induced conformational changes in Leishmania infantum kinetoplastid membrane protein-11 - Miguel Angel Fuertes; José Manuel Pérez; Manuel Soto; Manuel Carlos López; Carlos Alonso (JBIC Journal of Biological Inorganic Chemistry, 2001)

The Human Papillomavirus Type 16 E5 Protein Modulates ERK1/2 and p38 MAP Kinase Activation by an EGFR-Independent Process in Stressed Human Keratinocytes - Kerstin Crusius; Isabel Rodriguez; Angel Alonso (Virus Genes, 2000)